Multi-dimensional simulations of bow shocks of massive, high-velocity runaway stars - Ramalatswa, Katlego Jafta (Department of Astronomy, 2023)
Stellar bow shocks result from the supersonic collision of stellar winds ejected by runaway stars and the interstellar medium (ISM). Studying their properties provides constraints on mass-loss rates, stellar wind velocities and the properties of the ISM. In this work, we study the formation of bow shocks from stars at the tail end of the runaway velocity distribution which we refer to as high-velocity runaway (HVR) stars. We use PLUTO, a magneto-hydrodynamics grid code, to simulate these bow shocks, performing hydrodynamic simulations in 2- and 3-dimensions, while including thermal conduction and detailed radiative cooling/heating. Extensive 3D freely expanding stellar wind models testing the numerics in PLUTO, e.g., grid geometries, solvers, limiters and convergence with resolution are presented. Further 2D adiabatic, thermal conduction and radiative cooling models for runaways moving at v∗ ∼ 40 km/s were conducted, and verified through comparison with analytic models and the literature. We then present the main focus of this work, our results for HVRs with space velocities of 200 km/s and 400 km/s, for stars in both main-sequence (MS) and red-supergiant (RSG) phases, and moving through different ISM phases: the hot ionized medium (HIM), H II regions (HII), warm neutral medium (WNM) and cold neutral medium (CNM). We demonstrate that the star's evolutionary phase; ISM phase; relative space velocity; thermal conduction and radiative cooling/heating, all have significant impact on the morphology and evolution of the bow shocks. We studied all the HVR bow shock models focusing primarily on the properties of the reverse shock and the contact discontinuity. We also studied the development of instabilities and numerical artifacts. The latter we suggest is mainly due to the carbuncle phenomenon, while the former are due to the non-linear thin-shell, Kelvin-Helmholtz and Rayleigh–Taylor instabilities. Furthermore, we discuss results from comparing 2D and 3D models to determine the effect of dimensionality on the growth of these instabilities and the carbuncle phenomenon. This study serves as the foundation of future work in which we will i) investigate the potential of observing these HVR bow shocks by making multi-wavelength estimates using established radiative transfer codes (e.g., TORUS) and producing synthetic images at different wavelengths (e.g., ultraviolet, Hα, infrared and radio), ii) couple these hydrodynamic models to established stellar evolutionary codes (e.g., MESA), and iii) include the effect of magnetic field and stellar rotation.